Analisis Kausalitas Inflasi dan Jumlah Uang Beredar di Indonesia Periode Tahun 2000.1"“2014.4 - Afrizal, Afrizal (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
There is often a debate about causality between money supply and inflation. The purpose of this study is to analyze the causality, whether the money supply affects inflation or vice versa. Analytical tool used is unit root test, integration degree test, causality test with granger causality technique and cointegration approach. The result of unit root test data is not stationary, after test of stationary data continued at level 1 (first difference). The result of granger causality test with lag 12 indicates that the money supply has an effect on inflation rate in Indonesia, and vice versa means there is a mutual relationship. And based on Johanson's cointegration test shows that mutual cointegration means having long-term equilibrium relationship as desired by the theory.